Comparison of inhaled corticosteroids and leukotriene receptor antagonists in adolescents and adults with mild to moderate asthma: a meta‐analysis. (23rd March 2012) - Yang, Danlei; Luo, Hao; Wang, Jianmiao; Bunjhoo, Hansvin; Xu, Yongjian; Xiong, Weining
Abstract Introduction: Inhaled corticosteroids (ICS) and oral leukotriene receptor antagonists (LTRA) are effective drugs used in the management of asthma as controller monotherapy in adolescents and adults, although there are debates as to which one is better. Objectives: To thoroughly compare the efficacy and tolerability of ICS vs LTRA in adolescents and adults with mild to moderate asthma. Methods: Relative database were searched for the review. Randomized controlled trials of more than or equal to 4 weeks' treatment duration comparing ICS with LTRA were reviewed. Results and Conclusion: Twenty‐four trials with 6197 randomized adolescents and adults with mild to moderate asthma met the inclusion criteria with a minimum duration of 4 weeks' treatment. Significant differences favouring ICS were found in all indices of pulmonary function. Other significant benefits of ICS were shown in symptoms, nocturnal awakenings, rescue‐medication use, symptom‐free days and quality of life. As to each special symptom of adverse effects, ICS was similar to LTRA in the incidence of headache, nausea and throat discomfort, but significantly higher in the incidence of hoarseness and oral pharyngeal candidiasis. Concerning withdrawal because of adverse events potentially related to treatment, ICS was similar to LTRA but significantly superior to LTRA in decreasing the asthma exacerbations or attacks during the treatment period. These results show that ICS may be the better drug in terms of efficacy and tolerability, except hoarseness and oral pharyngeal candidiasis, and should thus have priority over LTRA in asthma monotherapy in adolescents and adults. Please cite this paper as: Yang D, Luo H, Wang J, Bunjhoo H, Xu Y and Xiong W. Comparison of inhaled corticosteroids and leukotriene receptor antagonists in adolescents and adults with mild to moderate asthma: a meta‐analysis. Clin Respir J 2013; 7: 74–90.